CORRELATION STRATEGY FOR DETERMINING THE PARAMETERS OF THE REVISED HELGESON-KIRKHAM-FLOWERS MODEL FOR AQUEOUS NONELECTROLYTES - Plyasunov A.V.; Shock E.L. (My University, 2001)
The main goal of this study is to revise the correlation algorithm for estimating parameters of the revised Helgeson-Kirkham-Flowers (HKF) model for aqueous nonelectrolyte solutes. The basis for the revision is the analysis of a large body of experimental values of the standard partial molar heat capacities and volumes of aqueous nonelectrolytes published mainly during the last decade. Unlike earlier estimation methods, we show that one of the most useful properties for developing correlations for uncharged species is the standard Gibbs energy of hydration of a solute at 298.15 K and 0.1 MPa, ΔhGo, which reflects the strength of water-solute interactions. Explicit correlations with ΔhGo seem to provide reliable means to estimate the “solvation” parameter ω and the “caloric” parameter c2 in the revised HKF model. “Volumetric” parameters a1 to a4 depend on both the size of a solute and its standard Gibbs energy of hydration. It is expected that the revised estimation strategy will improve the reliability of predictions of thermodynamic properties of aqueous nonelectrolytes in the framework of the revised HKF model. A related problem is the temperature and density ranges of the applicability of the model for uncharged species. A comparison of experimental properties and those fitted in the framework of the revised HKF model made in this study or in articles published elsewhere shows that the model can be used along the saturation vapor-liquid curve of pure water in the density region sufficiently remote from the critical point of water, say up to 630 K. At densities above 500 to 600 kg · m−3 the range of applicability of the revised HKF model for uncharged species may extend up to higher temperatures. At temperatures up to 500 K at pressures up to 50 MPa, the revised HKF model is capable of excellent description of the standard thermodynamic properties of aqueous nonelectrolytes, except in the narrow temperature range below 280–290 K.